The Effectiveness of Reading Comprehension Skills Through Survey, Question, Read, Recite, Review Reading Techniques in Islamic Religious Education Subjects Assisted by Prezi in Grade V Elementary Schools - Puri, Roza Melinda; Hermawan, Jody Setya; Muhisom, Muhisom (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
The purpose of this study was to analyze the effectiveness of reading comprehension skills through the survey, question, read, recite, review (SQ3R) reading technique in Islamic Religious Education subjects assisted by prezi in grade V of elementary school. The method in this study was a quasi-experiment with a nonequivalent control group design. The population of this study was 74 students with a sample of 49 students determined using purposive sampling. The data collection technique in this study used tests and non-tests. Data analysis used a linear regression test with a prerequisite test using the normality test (Shapiro Wilk) and the homogeneity test (Levene test) through SPSS software version 29. The results showed that F-Count obtained while F-table obtained . Based on the R-Square test of  while the rest of The effectiveness of N-Gain after being given treatment using the SQ3R reading technique assisted by prezi showed that it was quite effective to be used in the experimental class with a value of 60.18%. It can be concluded that the results of this linear regression test prove that there is an effectiveness of reading comprehension skills of PAI Class V through the SQ3R reading technique assisted by prezi.